2000
DOI: 10.1038/labinvest.3780202
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of PTHrP and Bcl-2 Expression Characterizes the Progression of Osteochondroma towards Peripheral Chondrosarcoma and Is a Late Event in Central Chondrosarcoma

Abstract: SUMMARY:Chondrosarcomas are malignant cartilage-forming tumors arising centrally in bone (central chondrosarcoma) or within the cartilaginous cap of osteochondroma (peripheral chondrosarcoma). For hereditary multiple osteochondromas, two responsible genes, EXT1 and EXT2, have been cloned. Their recently elucidated role in heparan sulfate biosynthesis and Hedgehog diffusion leads to the hypothesis that EXT inactivation affects fibroblast growth factor (FGF) and Indian Hedgehog (IHh)/parathyroid hormone-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
121
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(135 citation statements)
references
References 36 publications
13
121
1
Order By: Relevance
“…31 Next to the H&E, Periodic acid-Schiff and Masson's trichrome stainings to assay the histology of the xenografts, the slides were stained with all antibodies listed in Table 3, which also summarizes the IHC conditions. All stainings in this study were independently evaluated by two pathologists (IM and ALLB) as previously described in detail.…”
Section: Tissue Array Constructionmentioning
confidence: 99%
“…31 Next to the H&E, Periodic acid-Schiff and Masson's trichrome stainings to assay the histology of the xenografts, the slides were stained with all antibodies listed in Table 3, which also summarizes the IHC conditions. All stainings in this study were independently evaluated by two pathologists (IM and ALLB) as previously described in detail.…”
Section: Tissue Array Constructionmentioning
confidence: 99%
“…4 Antigen retrieval was performed by boiling tissue sections in citrate buffer, pH 6.0, in a microwave oven for 10 seconds. Sections from CB and CMF series were then incubated overnight with anticathepsin K 17,18 It has been demonstrated that this scoring system is highly reproducible on decalcified bone tumor specimens. 4,18 The cellular localization (nuclear, cytoplasmic, and membranous) of immunopositivity was also noted.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Sections from CB and CMF series were then incubated overnight with anticathepsin K 17,18 It has been demonstrated that this scoring system is highly reproducible on decalcified bone tumor specimens. 4,18 The cellular localization (nuclear, cytoplasmic, and membranous) of immunopositivity was also noted. Scores that were generated with the same evaluation system for p16INK4A and cyclin D1 (CCND1) in CMF and HGCCS were available from previous studies.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Skeletal deformities can lead to functional problems and morbidity due to the entrapment of blood vessels, nerves and tendons. The possibility of transformation into a low-grade chondrosarcoma increases to 5 % in MHE [4]. While the disease can occur spontaneously, it has been estimated that 80 % of affected individuals have a positive family history with varied penetrance among affected members [28,34].…”
Section: Multiple Hereditary Exostosesmentioning
confidence: 99%